Recent development on library space and the satisfaction of academic library users need / Nur Aina Aliaa Ahmad Latfi. - Ahmad Latfi, Nur Aina Aliaa (Universiti Teknologi MARA Cawangan Selangor, 2016)
This paper aims to discuss on the previous and current study of the library space in the academic library. To make sure the reader fully understand about the topic, information regarding the academic library and library space are been discussed in details. Furthermore, in this article information regarding the history of library space also are been available for the users to get some knowledge on the development of library space in the academic library. Besides that, there is a section where the reader can know about what are the factors that contribute to the need of library space in the academic library. Knowing about the factors which is the reducing number of gate count and circulation activities the academic library have shift and change the traditional function of library that storing material to the need of providing various space in supporting the process of effective learning and teaching environment. Having the various spaces by fully understanding the need of user will attract the user’s attention in the use of library. Additional information regarding the importance of library space in academic library also have been stated in order to make reader especially the librarian become aware on the effective library design by knowing the space that are required to be available in the library. If the library have consider all the need of their users this indirectly can tackle the issues that been arise in the academic libraries.